The vitality of ice and bone: known uncertainty and awareness in change through Dolpo, Nepal - Pierce, Gregory Edward, author; Snodgrass, Jeffrey G., advisor; Sherman, Kathleen P., committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2012)
At least one thousand years of caravanning yaks through the remote Himalayas have significantly shaped the practices of the Dolpo-pa, a culturally Tibetan population dwelling through the highlands of Midwestern Nepal. In turn, those practices have significantly affected how the Dolpo-pa conceptualize their world, the models by which they frame the experiences that effect those practices being directly and continuously synergized with the ecological realities of the existential present in persistently confirming, contesting or altering their awareness of those experiences. Physical reality at the biometabolic scale of ecological processes, therefore, which is as a rule perfunctorily and uncritically framed by observers descended from the specific histories of the European Enlightenment as the second-order reification labeled the environment, is schematized by the Dolpo-pa as something more like an "entanglement" in the uncertainty inherent to dwelling through that scale. As such, unlike the Cartesian divide elemental to the Western model that distorts reality by a cognitive trick of circular framing in reifying second-order conceptualizations and taking those reifications as first-order realities in the world, ethnographic evidence indicates that the Dolpo-pa culturally model themselves as unique and distinct as humans but not as separate from their domain of metabolic entanglement. The difference in these representations is significant, not only because it highlights the emergent cultural model of the Dolpo-pa after extended engagement within that unforgiving mountain environment but also because it suggests what is being lost with the increasing contravention of the Western model of development into that domain. The Dolpo-pa's increasing acquiescence to the distortions of that model is beginning to disentangle at very basic levels their unique awareness, which is especially evident in new forms of social fragmentation that have only since around 2005 begun to influence how individuals in Dolpo constellate schemas of intra-entanglement arrangements and extra-entanglement connotations there. Worryingly, such new, second-order constellations have been concurrent with an increasing decline in the reliability of deep-rooted cultural models of known ecological uncertainties to effectively frame recent experiences with rapidly changing phenological conditions as average weather patterns (i.e. climate) have steadily altered in recent years. The Dolpo-pa's cultural model of entanglement is unfortunately incapable of proficiently conceptualizing let alone adequately representing and responding to changes at the technometabolic scale of industrial processes, whence such phenological changes have originated but at which few among the Dolpo-pa have experience or proficiency negotiating. This thesis concludes with a brief discussion of how continued decline in the efficacy of the Dolpo-pa's cultural model of entanglement is progressively leading to greater existential dissonance, a concept introduced here in conclusion that qualitatively gauges how such disentanglement gives rise to an increased likelihood of physical loss of life or livelihood within experiences no less physically entangled at the scale of ecological processes.